Front Cover: Design of a Full‐Consensus Glutamate Decarboxylase and Its Application to GABA Biosynthesis (ChemBioChem 8/2022). (5th November 2021) - Takagi, Hiroshi; Kozuka, Kohei; Mimura, Kenta; Nakano, Shogo; Ito, Sohei
Abstract : Glutamate decarboxylase (GAD) is a remarkable biocatalyst for the synthesis of γ‐amino butyric acid (GABA) from l ‐glutamate. In this study, artificial GAD named FcGAD (full consensus glutamate decarboxylase) was designed by consensus protein design. FcGAD exhibits suitable properties for application in GABA biosynthesis. This Front Cover (created by Takashi Tsujino, Science Graphics. Co., Ltd.) highlights the design concept and application of FcGAD to the biosynthesis. More information can be found in the Full Paper by S. Nakano, S. Ito et al.